BAKTERI SELULOLITIK SERASAH DAUN MANGROVEDI PULAU BANGKA - Ardiansyah Kurniawan; Asep Awaludin Prihanto; Suci Puspitasari; Andi Kurniawan; Euis Asriani; Abu Bakar Sambah (Faculty of Science and Technology University Ibrahimy, 2018)
The study aimed to obtain isolate of cellulolytic bacteria from leaf litter on mangrove in Bangka Island. Sampling was conducted on mangroves in Sungailiat, Bangka and Tukak Sadai, South Bangka district. The isolation was carried out using 1% enriched agarmedia of Carboxymetyl Cellulose (CMC). The bacterial isolates were tested with cellulolytic growth on 1% enriched CMC agar medium and lugol added at 72 hours. The clear zone resultingindicates cellulose degradation ability. The positive isolate of cellulolyticwas identified by biochemical tests. 1 of 5 isolates in Sungailiat positive cellulolytic mangroves and identified as Bacillus subtilis. 2 of 5 isolates in mangrove Tukak Sadai is positive as a cellulolytic bacteria and identified as Staphylococcus saproviticus and Bacillus cereus.